Teachers' Perspectives on Primary School Students' Speaking and Presenting Skills: A Survey Study - Adrias; Mansurdin; Yunisrul; Agus Ruswandi; Fadhilah Majid (Universitas Negeri Malang, 2026)
Abstract: Speaking and presenting are learning outcomes that present greater challenges than other elements as they require students to possess both adequate verbal proficiency and psychological readiness. This study aims to describe teachers' perceptions of student achievement in speaking and to identify the factors perceived to influence these outcomes. A quantitative survey method was employed, utilizing questionnaires for data collection. The respondents consisted of 161 fifth and sixth-grade elementary school teachers in Padang City, selected through multistage random sampling. Data were analyzed using descriptive statistics. The results indicate that the overall achievement level of speaking and presenting in Phase C is 77.90%, categorized as